HBR guide to persuasive presentations - Duarte, Nancy. (Harvard Business review guides., 2012)
Terrified of speaking in front of a group? Or simply looking to polish your skills? No matter where you are on the spectrum, this guide will give you the confidence and the tools you need to get results. Learn how to wIn over tough crows, organize a coherent narrative, create powerful messages and visuals, connect with and engage your audience, show people why your ideas matter to them, and strike the right tone, in any situation.